Characterization of fungus‐specific microsatellite markers in the lichen fungus Usnea subfloridana (Parmeliaceae)1. (10th July 2014) - Tõrra, Tiiu; Cornejo, Carolina; Cheenacharoen, Saran; Dal Grande, Francesco; Marmor, Liis; Scheidegger, Christoph
Abstract : Premise of the study: Microsatellite loci were developed for the haploid lichenized fungal species Usnea subfloridana to study its population subdivision and the species' response to forest disturbance, fragmentation, and environmental pollution. Methods and Results: We developed 14 polymorphic microsatellite markers using 454 pyrosequencing data of U. subfloridana . The number of alleles per locus ranged from three to 15, and Nei's unbiased gene diversity averaged over nine markers without null alleles ranged from 0.64 to 0.67. Evaluation of the cross‐species amplification in U. glabrescens and U. wasmuthii indicates that these markers are also informative in other Usnea species. Conclusions: These markers will allow us to investigate the effects of forest management and environmental pollution on genetic population structure of U. subfloridana and closely related species. Moreover, they will help facilitate phylogeographic studies of U. subfloridana across the species' distribution area in Europe.